Effect of Two Weeks Scapular Stabilisation Exercises, Upper and Lower Limb Plyometrics as a Part of Warm up on Cricket Medium Paced Bowlers: A Research Protocol - Basavaraj S Motimath; Sanjiv Kumar (Journal of Clinical and Diagnostic Research)
Introduction: Shoulder injuries are common in cricket. Such injuries can result from an ineffective training routine, traumatic injury, and micro-trauma-induced muscle strains. Scapular stabilising exercises should be prescribed during the early part of a shoulder rehabilitation programme to increase the strength of the upper limb musculature and prevent re-injury. Need of the study: Upper and lower limb plyometrics involve explosive, high-intensity exercises that can improve power, speed, and agility, which are crucial for bowlers to deliver fast and accurate deliveries. Therefore, studying the effect of a two-week training programme consisting of scapular stabilisation exercises and upper and lower limb plyometrics as part of a warm-up routine on medium-paced bowlers can provide valuable insights into enhancing their performance and reducing the risk of injury. The effectiveness of various training programmes on medium-paced bowlers’ performance is an area of ongoing research, and there is a need to investigate the potential benefits of incorporating scapular stabilisation exercises and upper and lower limb plyometrics into their warm-up routine. Aim: To evaluate the effect of two weeks of scapular stabilisation exercises with upper limb plyometrics versus scapular stabilisation exercises with upper and lower limb plyometrics as part of a warm-up on bowling speed in medium-paced cricket bowlers. Materials and Methods: This research protocol is planned to conduct a randomised clinical trial in Belagavi, Hubli, and Dharwad in Karnataka, India, and will employ a randomised, parallel-armed clinical experimental design. The duration of the study will be approximately four years, from January 2023 to February 2027. A total of 66 male cricketers from various KSCA-registered cricket clubs in Belagavi, Hubli, and Dharwad, with medium-paced bowling speed, aged between 18 and 35 years, will be randomly allocated to either a scapular stabilisation and upper limb plyometric group (N=33) or a scapular stabilisation upper limb and lower body plyometric group (N=33) for a period of two weeks (6 times per week). Bowling speed will be used to determine the speed of the ball, the one-minute pull-up test will be used to determine the strength of the upper limb, the vertical jump test will be used to determine the power of the lower limb, a goniometer will be used to determine shoulder range of motion and Glenohumeral Internal Rotation Deficit (GIRD), and target-based bowling accuracy will be used to determine bowling accuracy for one over. Inferential as well as statistical methods will be used to analyse the gathered data. A test for normal distribution will be conducted to determine whether non-parametric tests (Wilcoxon signed rank test, Mann-Whitney U test) will be performed. A probability value of <0.05 will be considered statistically significant.